IMF Research Bulletin, March 2014. (IMF Research Bulletin; IMF Research Bulletin ;, 2014)
The Research Summaries in the March 2014 Research Bulletin focus on efficiency of health expenditure (Francesco Grigoli and Javier Kapsoli) and employment growth in European Union countries (Bas B. Bakker and Li Zeng). The Q and A article looks at 'Seven Questions on Financial Interconnectedness' (Co-Pierre Georg and Camelia Minoiu). The Research Bulletin also includes a listing of IMF Working Papers, Staff Discussion Notes, and Recommended Readings from the IMF Bookstore. Information on the IMF Economic Review-the research journal of the IMF-is also provided.